THE EFFECT OF USING NAPIER ROD MEDIA ON MULTIPLICATION MATERIAL ON THE LEARNING OUTCOMES OF GRADE III STUDENTS OF STATE ELEMENTARY SCHOOL 2 LAMCOT ACEH BESAR - Amalia, Nana; Fitri, Aida; Fauzi, Fauzi (Universitas Syiah Kuala, 2024)
This research aims to determine the effect of using napier rod media in multiplication material on the learning outcomes of class III students at SD Negeri 2 Lamcot Aceh Besar. This research uses a quashi-experimental quantitative (pretest posttest) control group design. The population in this study were all class III students at SD Negeri 2 Lamcot Aceh Besar with a sample of class III A and III B students. Data were collected using tests in the form of pretest and posttest. The data analysis technique use the N-gain test and independent t-test with the help of IBM SPSS STATISTIC Version 26 for Windows. The research result show that the significance result (2-tailed) is 0.00. Where 0.00 0.05 then the conclusion of the results in decision making is that Ha is accepted and H0 is rejected. Thus, it can be concluded that there is an influence of the use of napier rod media in multiplication material on the learning outcomes of class III students at SD Negeri 2 Lamcot Aceh Besar.